Evaluation of Community-Based Disease Surveillance System in the Central Region of Ghana - Adjei Benjamin (University of Cape Coast, 2024)
The study sought to evaluate the community-based surveillance (CBS) system in the Central Region of Ghana. A mixed-method approach was used for the study. Questionnaires were used to assess CBSVs and focal persons quantitatively. A total of 1381 communities were accessed and out of these, 898 had CBSVs which they were interviewed. Also, the performance of 477 focal persons from Community-based Health Planning and Services (CHPS) compounds, sub-districts, and district levels on supportive functions to CBSVs was assessed. Moreover, an interview guide was used to ascertain the views of opinion leaders on the CBS system. SPSS Version 22 was used to analyse the quantitative data while NVivo 10 was used to analyse the qualitative data. The results showed that CBSVs' knowledge of priority diseases and events is low; CBSVs received low support from facility surveillance focal persons; CBSVs' performance on their core and quality surveillance functions was low. CBSVs in the urban areas performed well in reporting while CBSVs in the rural areas did well in providing feedback. The facility focal persons’ performance on supportive functions to the CBSVs was also low but had a high impact on CBSVs' work. Opinion leaders perceived inadequate motivation to CBSVs; conflicts with nurses; frequent travel; aging and late response to CBSV reports by health authorities affect CBSVs work. It is recommended that the District Health Management Teams (DHMTs) should train CBSVs and health staff on priority diseases and events; mobilise resources for CBSVs work; create an electronic reporting tool for CBSVs; improve feedbacks and reporting in urban and rural communities respectively; support opinion leaders to address conflicts, late response to reports and inadequate motivation to CBSVs.
xv, 263;, ill
Keywords: community based evaluation disease surveillance